Regional Personalized Electrodes to Select Transcranial Current Stimulation Target - Tecchio, Franca; Cancelli, Andrea; Cottone, Carlo; Tomasevic, Leo; Devigus, Barbara; Zito, Giancarlo; Ercolani, Matilde; Carducci, Filippo (Frontiers in Human Neuroscience, 2013)
Rationale Personalizing transcranial stimulations promises to enhance beneficial effects for individual patients. Objective To stimulate specific cortical regions by developing a procedure to bend and position custom shaped electrodes; to probe the effects on cortical excitability produced when the properly customized electrode is targeting different cortical areas. Method An ad-hoc neuronavigation procedure was developed to accurately shape and place the personalized electrodes on the basis of individual brain magnetic resonance images (MRI) on bilateral primary motor (M1) and somatosensory (S1) cortices. The transcranial alternating current stimulation (tACS) protocol published by Feurra and coll. (2011) was used to test the effects on cortical excitability of the personalized electrode when targeting S1 or M1. Results Neuronal excitability as evaluated by tACS was different when targeting M1 or S1, with the General Estimating Equation model indicating a clear tCS Effect (p < 0.001), and post-hoc comparisons showing solely M1 20Hz tACS to reduce M1 excitability with respect to baseline and other tACS conditions. Conclusions The present work indicates that specific cortical regions can be targeted by tCS properly shaping and positioning the stimulating electrode. Significance Through multimodal brain investigations continuous efforts in understanding the neuronal changes related to specific neurological or psychiatric diseases become more relevant as our ability to build the compensating interventions improves. An important step forward on this path is the ability to target the specific cortical area of interest, as shown in the present pilot work.